“COVID-19” MEME IN SOCIAL MEDIA: STUDY OF ROLAND BARTHES SEMIOLOGY - Tiya Agustina; Siti Isnaniah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT The objective of this research is to reveal the meaning of Covid-19 memes in social media using study of Roland Barthes semiology. In addition, this research also explains the social representation in Covid-19 memes. The method of the research is qualitative descriptive using technical analysis of Roland Barthes semiology. The technique of collecting data is based on two resources. The primary data are collections of memes about Covid 19 in some social media, such as Instagram, Facebook, and Web Blog. The secondary data are references supporting the topic of the research. In validity technique, the primary data are collected based on the topic of the discussion. After that, the data are processed descriptively by explaining, and comparing the information gained from many resources. Then, the data are reduced and presented. The result of the study shows that the creators tried to reveal social condition through Covid-19 memes. The social conditions were presented in some types of memes, namely critical memes, parodist memes, and motivational memes. In relation to meaning presentation, some social problems were revealed Covid-19 memes. Keywords: Meme, Covid-19, Social Media, Roland Barthes Semiology